Pyridinium Chlorochromate Catalyzed Oxidation of Toluenes to Aromatic Carboxylic Acids with Molecular Oxygen in Sub-critical Water - Ozen, Recep (Asian Journal of Chemistry, 2014)
Oxidation of substituted toluenes in the presence of molecular oxygen with pyridinium chlorochromate in subcritical water under the nitrogen atmosphere at 120 °C to the corresponding substituted benzoic acids were investigated. Substituted toluenes were directly oxidized to their carboxylic acids in excellent yields (> 70 %).